Paghalungkat ng mga Ugat: Ang Paggalugad at Pagsipat sa Pagpili ng mga Artikulong Nailathala sa Dalumat E-Journal mula 2010 hanggang 2022 (Unearthing the Roots: An Exploration and Examination of the Selection of Articles Published in the Dalumat E-Journal from 2010 to 2022) - Reyes, Jessica May; Victoria, Vasil (Social Sciences and Development Review, 2024)
This study is focused on exploring the process of how the articles in the Dalumat E-Journal (DEJ) of Networked Learning PH from 2010 to 2022 were published. This was inspired by Eilene Narvaez’s exploration of the entire process of choosing the winner for the “Salita ng Taon,” by the Filipinas Institute of Translation (FIT). Furthermore, this research used the Mixed Method design which aided the researcher in analyzing all articles that are available from the official website of Philippine E-Journals. By using Critical Discourse Analysis, the researcher had the chance to look into all the factors that influenced the selection of the articles published in DEJ. In this study, it was discovered that despite all the changes brought by technology and modernization happening in the present, the art of conventional writing is still sought in journal publications. In general, it would still be best for the readers and/or aspiring contributors to reflect on what is the real foundation of good writing—reading. The intellectualization of Filipino as a language is a long road to take but it does not mean that we cannot do anything. Through small steps, we, as citizens can do something like using our language, especially in research publications. We always must start somewhere to achieve the huge goals for our country
Keywords: Electric Journal (E-Journal); Discourse; Intellectualization; Refereed Journal; Publication